Rekayasa Kayu Eucalyptus pellita F. Muell Dengan Teknologi Oil Heat Treatment (OHT) : Wood Engineering Eucalyptus Pellita F. Muell With Oil Heat Treatment (Oht) Technology - Siska, Grace; Christy, Eva Oktoberyani; Sihombing, Markus; Rizal, Moh; Pidjath, Chartina (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Eucalyptus pellita F. Muell is a plant that is widely developed in Indonesia's Industrial Plantation Forest (HTI), because this plant is a fast growing wood. Eucalyptus pellita F. Muell wood has weaknesses in terms of durability quality and strength of its wood. Therefore, an environmentally friendly and effective application of technology is needed. Oil Heat Treatment (OHT) is one of the environmentally friendly and appropriate wood technologies because there are no chemicals during the treatment process. This study aims to determine the effect of the duration of OHT time of 1 hour, 2 hours and 3 hours with a temperature of 200 ± 2°C on changes in the physical properties of wood mechanics of Eucalyptus pellita F. Muell. The research results indicate that the heat treatment method known as Oil Heat Treatment (OHT) using used cooking oil can reduce the moisture content of wood over the duration of heating, as well as increase the density, Modulus of Elasticity (MoE), and Modulus of Rupture (MoR) of Eucalyptus pellita F. Muell wood, although the statistical analysis in the study showed that the treatment did not have a significant effect.